Analisis SWOT Potensi Desa dan BUMDes Kedarpan - Joval Ifghaniyafi Farras; Raden Rifqi Dwi Santo (PT PUSTAKA CENDEKIA GROUP, 2024)
SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) is a critical strategic planning tool for evaluating the potential of villages and Village-Owned Enterprises (BUMDes) in Indonesia. BUMDes is a government initiative in empowering the economy of village communities, utilizing local resources to encourage rural entrepreneurship. This article highlights the results of a SWOT analysis of BUMDes in Kedarpan Village, showing that development prospects have not been optimal in various time periods. SWOT is used to formulate BUMDes management strategies, accelerate development, and improve performance during the COVID-19 pandemic. Kedarpan Village has agricultural and MSME potential which includes superior products such as white pepper and snacks made from cassava. BUMDes, such as Village Internet and chicken farms, play an important role in managing natural resources and empowering communities. This article concludes the need for BUMDes management training and further activities from the village government in building communication networks with external parties. Recommendations involve developing human resource competencies, marketing management, and collaboration with other parties to support sustainable management of Kedarpan Village and BUMDes.